2014
DOI: 10.1111/joim.12217
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil supplementation induces expression of genes related to cell cycle, endoplasmic reticulum stress and apoptosis in peripheral blood mononuclear cells: a transcriptomic approach

Abstract: BackgroundFish oil supplementation has been shown to alter gene expression of mononuclear cells both in vitro and in vivo. However, little is known about the total transcriptome profile in healthy subjects after intake of fish oil. We therefore investigated the gene expression profile in peripheral blood mononuclear cells (PBMCs) after intake of fish oil for 7 weeks using transcriptome analyses.DesignIn a 7-week, double-blinded, randomized, controlled, parallel-group study, healthy subjects received 8 g day−1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 53 publications
2
43
1
Order By: Relevance
“…The steatotic hepatocyte appears to be more susceptible to apoptosis. A previous study reported that fish oil can modulate the redox environment by increasing apoptosis, which is mediated by ROS (Sanders et al, 2004), but other reports concluded fish oil has the ameliorating effects of oxidative stress and apoptosis (Myhrstad et al, 2014;Hong et al, 2015). The contradiction might be due to the dose because excess n-3 HUFA led to lipid peroxidation and oxidative stress in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…The steatotic hepatocyte appears to be more susceptible to apoptosis. A previous study reported that fish oil can modulate the redox environment by increasing apoptosis, which is mediated by ROS (Sanders et al, 2004), but other reports concluded fish oil has the ameliorating effects of oxidative stress and apoptosis (Myhrstad et al, 2014;Hong et al, 2015). The contradiction might be due to the dose because excess n-3 HUFA led to lipid peroxidation and oxidative stress in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…Gene transcripts related to processes such as cell division, ‐proliferation, and ‐growth and apoptosis were downregulated by ND compared to CD (Tables and ), indicating that the intake of ND has an impact on basic cellular processes. Interestingly, the intake of fish oil has previously been shown to modulate expression of genes related to cell cycle and apoptosis . Whether the effects reported in the current study are specific to n‐3 fatty acids remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…A good source of cells to study the abovementioned processes are peripheral blood mononuclear cells (PBMCs), which have proven useful for the determination of the effects of nutritional interventions on gene expression profiles . These cells are a subset of circulating white blood cells, which are straightforward to collect during human intervention studies as they can be easily isolated from blood.…”
Section: Introductionmentioning
confidence: 99%